XFEM based seismic potential failure mode analysis of concrete gravity dam–water–foundation systems through incremental dynamic analysis. (1st September 2015) - Wang, Gaohui; Wang, Yongxiang; Lu, Wenbo; Zhou, Chuangbing; Chen, Ming; Yan, Peng
Highlights: Cracking response of dam–reservoir–foundation systems is investigated by the IDA. 40 real records with each scaled to 8 levels are selected as seismic excitations. The combined XFEM and Lagrangian FE method is presented for seismic crack analysis. Five typical failure modes of dams are generalized from 320 simulation cases. Abstract: As revealed by the structural damage of concrete dams (e.g. Hsinfengkiang, Koyna, Sefid-Rud) arising in recent earthquakes, cracking damage would probably occur inside concrete dams when subjected to strong ground motions. This phenomenon is caused by the low tensile resistance of concrete. Research on the cracking damage process and failure modes of concrete gravity dams subjected to strong earthquakes is crucial to a reasonable assessment of the seismic safety of dams. In this paper, the extended finite element method (XFEM) is presented to describe the crack propagation within concrete gravity dams subjected to earthquake loads. Moreover, the interaction between the impounded water and the dam–foundation system is explicitly taken into account by modeling the reservoir water with two-dimensional fluid finite elements in the Lagrangian formulation. In order to validate the proposed algorithm, seismic crack analysis is performed to investigate the failure modes of the Koyna dam–reservoir–foundation system under the 1967 Koyna earthquake. It shows that the cracking damage profile obtained from the proposed XFEM framework agrees well with that reported in the literature. With the validated algorithm, we further apply it to study the potential failure modes of the Guandi concrete gravity dam. Seismic cracking response of concrete gravity dams considering the effects of the dam–reservoir–foundation interaction is obtained through the incremental dynamic analysis (IDA) based XFEM. 40 as-recorded accelerograms with each scaled to 8 increasing intensity levels are selected in this study. Based on the 320 numerical simulation results, typical failure processes and five potential failure modes of concrete gravity dams under the selected database of strong earthquake ground motions are presented.